2017
DOI: 10.1080/09638288.2017.1280545
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessment for rehabilitation of chronic illness and disability

Abstract: EMA is emerging as a novel modality of assessment in rehabilitation. Scientists and clinicians should consider incorporating this assessment approach as a rehabilitation tool that may more accurately assess the complex and dynamic nature of disability over the long-term through an objective and ecologically-valid data source. Implications for rehabilitation Ecological momentary assessment (EMA) has been underutilized in the rehabilitation field and should be considered by researchers and clinicians as a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…To our knowledge this is the first novel study which has explored the patients' perspective in their experience of participating in an EMA study and the impact it had on their daily lives. Due to recent eHealth drivers in healthcare we have observed an exponential growth in digitalised EMA studies in long-term conditions 9,17,33 however no study has of yet explored patients' own experience of participating in an EMA study. We observed that men derived benefit from tracking their real time data for different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge this is the first novel study which has explored the patients' perspective in their experience of participating in an EMA study and the impact it had on their daily lives. Due to recent eHealth drivers in healthcare we have observed an exponential growth in digitalised EMA studies in long-term conditions 9,17,33 however no study has of yet explored patients' own experience of participating in an EMA study. We observed that men derived benefit from tracking their real time data for different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The first recommendation is to consider triangulating the measurement of participation with complementary instruments and methods (e.g., using individualized outcome assessments along with static surveys of social participation, measuring lifespace in addition to social participation, and utilizing qualitative methods of interview and observation) to fully characterize participation and evaluate how an intervention may influence different aspects of participation. Ecological momentary assessment (EMA) is a promising method for measuring participation (McKeon, McCue, Skidmore, Schein, & Kulzer, 2018), in which mobile devices query participants at random points across a specified time period. Participants can be asked to report on activity, location, presence of others, mood, and level of difficulty, satisfaction, autonomy, meaningfulness, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…There is an extensive body of work pertaining to the use of EMA for a variety of health conditions and the general population across the lifespan (youth 20,21 to older adults 22 ; Figure 2(a) displays the range of conditions for which EMA has been used). EMA is an established methodology used to better understand the psycho-social components of chronic pain, 23 the contextual factors and affects surrounding eating and dietary intake behaviors, [24][25][26][27] the dynamics of mood disorders, [28][29][30] and the physical activity levels in non-disabled individuals. 17,18,31 However, EMA is strikingly underutilized in the field of rehabilitation.…”
Section: What Are the Benefits Of An Ecological Momentary Assessment mentioning
confidence: 99%